Assessing the prospect of a common health-related stigma reduction response: Cross-perspectives of people living with stigmatised health conditions in Indonesia. Issue 12 (2nd December 2021) - Rai, Sarju Sing; Syurina, Elena V.; Peters, Ruth M.H.; Irwanto, Irwanto; Naniche, Denise; Zweekhorst, Marjolein B.M.
ABSTRACT : This study explored the possibility of a common health-related stigma reduction intervention among people living with HIV, leprosy, schizophrenia and diabetes in Indonesia by assessing their perspectives towards others with the same (within group) and different health conditions (across groups), and willingness to participate in such a program. This mixed-methods study was conducted in West Java, Indonesia between March and June 2018. Eighty participants completed a survey with social distance scale (SDS), while 12 focus group discussion were conducted. Participants with HIV, leprosy and diabetes reported lower within-group SDS scores (4.14 ± 3.65; 4.25 ± 3.95; 7.23 ± 5.31, respectively) while those with schizophrenia reported the highest within-group SDS score (7.76 ± 4.63). Participants with diabetes reported a twofold higher across-group SDS score towards people with the other three health conditions ( p < 0.05). The qualitative findings showed that the perception of participants towards one another was shaped by knowledge, understanding and relatedness to the experience of living with health-related stigma. Overall, participants supported the idea of a common stigma reduction intervention for different health conditions, but recommended step-wise implementation of such interventions. Accordingly, this study recommends piloting a common stigma reduction intervention with special focus on fostering understanding, awareness and empathy between people living with different health conditions.